Reduced Serum Levels of Bone Formation Marker P1NP in Psoriasis - Mentzel, Julia; Kynast, Tabea; Kohlmann, Johannes; Kirsten, Holger; Blüher, Matthias; Simon, Jan C.; Kunz, Manfred; Saalbach, Anja (Frontiers in Medicine, 2021)
Psoriasis is a chronic inflammatory disease of the skin and joints. More recent data emphasize an association with dysregulated glucose and fatty acid metabolism, obesity, elevated blood pressure and cardiac disease, summarized as metabolic syndrome. TNF-α and IL-17, central players in the pathogenesis of psoriasis, are known to impair bone formation. Therefore, the relation between psoriasis and bone metabolism parameters was investigated. Two serum markers of either bone formation - N-terminal propeptide of type I procollagen (P1NP) or bone resorption - C-terminal telopeptide of type I collagen (CTX-I) - were analyzed in a cohort of patients with psoriasis vulgaris. In patients with psoriasis, P1NP serum levels were reduced compared to gender-, age- and body mass index-matched healthy controls. CTX-I levels were indistinguishable between patients with psoriasis and controls. Consistently, induction of psoriasis-like skin inflammation in mice decreases bone volume and activity of osteoblasts. Moreover, efficient anti-psoriatic treatment improved psoriasis severity, but did not reverse decreased P1NP level suggesting that independent of efficient skin treatment psoriasis did affect bone metabolism and might favor the development of osteoporosis. Taken together, evidence is provided that bone metabolism might be affected by psoriatic inflammation, which may have consequences for future patient counselling and disease monitoring.